Root morphology of Arabica coffee cultivars subjected to different spatial arrangements - Ronchi, Cláudio Pagotto; Sousa Júnior, José Márcio de; Ameida, Wellington Luiz de; Souza, Daniela Silva; Silva, Natália Oliveira; Oliveira, Leandro Barbosa de; Guerra, Antonia Miriam Nogueira de Moura; Ferreira, Paulo Afonso (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the morphological responses of the root system of four Arabica coffee cultivars subjected to different spatial arrangements. The adopted plant spacings were 0.40, 0.50, 0.60, 0.70, and 0.80 m between plants within rows, maintaining 3.8 m constant between rows. At 27, 35, and 39 months after transplanting, samples of soil+roots were collected at three surface positions in relation to plant stems and at three depths. Roots were washed, colored, digitalized, and processed with the Safira software. The Tupi RN IAC 1669‑13 cultivar showed a root system with superior morphological traits related to the absorption of nutrients and water, in comparison to those of the Catuaí Vermelho IAC 144, Catuaí Amarelo IAC 62, and Catuaí Amarelo IAC 32 cultivars, for all tested spatial arrangements. The reduction in spacing increases the amount of total root per soil volume unit, without affecting the morphological quality of the root system, nor deepening it. The root systems of the evaluated cultivars are more abundant and show higher surface and specific length between adjacent plants, followed by the 0.25 and 0.50 m positions away from the coffee stem. The proportion of roots at the 0.1 m layer is higher than at the 0.4 m layer, for all plant spacings. Changes in spacings between plants within lines affect the morphology of Arabica coffee root system.